Incidental Finding of Wandering Spleen - Catalya Christina Cantika; Ekarini Aryasatiani; Tania; Ali Reza; Mahendro Aji Panuntun; Luminto (Indonesian Socety of Obstetrics and Gynecology, 2025)
Introduction: Wandering spleen (WS) is a rare case due to inadequate spleen binding ligaments, causing increased spleen hypermobility and displacement of the spleen from the left upper quadrant abdominal location. Case findings can be incidental or symptomatic with acute abdomen due to complications of WS cases. Case Report: A 36-year-old, gravida 3, para 1, abortus 0, at 41-42 gestational age woman presented at our hospital for planned cesarean section indicated for premature rupture of membranes and preeclampsia. Intraoperative findings revealed that the spleen was incidentally in the pelvic cavity, lateral to the uterus. There were no abnormalities of the spleen intraoperatively, and the patient did not show any complaints related to the abnormal location of the spleen. The patient was planned for Splenopexy to maintain the spleen function. Conclusion: WS cases are rare, with varied manifestations from asymptomatic to acute abdomen due to acute complications. This patient was asymptomatic, and the findings of the WS were incidental. The most common complications in WS cases are torsion and splenic infarction, with splenectomy as the main treatment. Asymptomatic patients are advised to undergo Splenopexy to maintain spleen function and reduce the risk of WS complications. Keywords: spleen, ectopic spleen, rare diseases, pregnancy.